Early anther ablation triggers parthenocarpic fruit development in tomato. Issue 6 (15th April 2013) - Medina, Mónica; Roque, Edelín; Pineda, Benito; Cañas, Luis; Rodriguez‐Concepción, Manuel; Beltrán, José Pío; Gómez‐Mena, Concepción
Summary: Fruit set and fruit development in tomato is largely affected by changes in environmental conditions, therefore autonomous fruit set independent of fertilization is a highly desirable trait in tomato. Here, we report the production and characterization of male‐sterile transgenic plants that produce parthenocarpic fruits in two tomato cultivars (Micro‐Tom and Moneymaker). We generated male‐sterility using the cytotoxic gene barnase targeted to the anthers with the PsEND1 anther‐specific promoter. The ovaries of these plants grew in the absence of fertilization producing seedless, parthenocarpic fruits. Early anther ablation is essential to trigger the developing of the transgenic ovaries into fruits, in the absence of the signals usually generated during pollination and fertilization. Ovaries are fully functional and can be manually pollinated to obtain seeds. The transgenic plants obtained in the commercial cultivar Moneymaker show that the parthenocarpic development of the fruit does not have negative consequences in fruit quality. Throughout metabolomic analyses of the tomato fruits, we have identified two elite lines which showed increased levels of several health promoting metabolites and volatile compounds. Thus, early anther ablation can be considered a useful tool to promote fruit set and to obtain seedless and good quality fruits in tomato plants. These plants are also useful parental lines to be used in hybrid breeding approaches.